2022
DOI: 10.26554/sti.2022.7.3.275-283
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Mg/Al-LDH Intercalated Metal Oxide (Mg/Al-Ni) to Improve The Performance of Methyl Orange and Methyl Red Dyes Adsorption Process

Abstract: Modification of Mg/Al-LDH intercalated metal oxide (Mg/Al-Ni) was successfully formed by the coprecipitation method at pH 10, which is indicated by the XRD diffraction, FTIR spectrum, and BET analysis. Mg/Al-LDH increased surface area after intercalated Ni from 8.621 m2/g to 9.821 m2/g and improved performance in process regeneration which can be used in the three cycles. Mg/Al-LDH after intercalated metal oxide (Ni) increases adsorption capacity of is 69.930 mg/g to 71.429 mg/g for methyl orange (MO) and 77.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Mg/Al LDH was synthesized by coprecipitation at pH 10 according to the modified procedure of Rahmadan et al [31] and Yuliasari et al [32]. The mole ratio of Mg 2+ /Al 3+ is 3 by mixing 0.75 M Mg(NO3)2.6H2O to 0.25 M Al(NO3)3.9H2O to form 100 mL of solution.…”
Section: Synthesis Of Mg/al Ldhmentioning
confidence: 99%
“…Mg/Al LDH was synthesized by coprecipitation at pH 10 according to the modified procedure of Rahmadan et al [31] and Yuliasari et al [32]. The mole ratio of Mg 2+ /Al 3+ is 3 by mixing 0.75 M Mg(NO3)2.6H2O to 0.25 M Al(NO3)3.9H2O to form 100 mL of solution.…”
Section: Synthesis Of Mg/al Ldhmentioning
confidence: 99%
“…Additionally, there are peaks around 1380 cm −1 , indicating the presence of CO 3 2− ions in the structures of these materials (Qin et al, 2023;Lv et al, 2022;Priatna et al, 2023). Spectral analysis of the materials showed characteristic peaks in all three materials, such as O H bending at a wave number around 1630 cm −1 and metal oxygen bonds (M O) at wave numbers around 600 cm −1 and 830 cm −1 , indicating the presence of specific functional groups and metaloxygen bonds in the samples such as Zn O, Mg O, Ni O, and Al O (Yuliasari et al, 2022;Intachai et al, 2021;Mahjoubi et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The adsorption process was carried out by adding 0.02 g of adsorbent to as much as 20 mL of a 60 mg/L malachite green dye solution, then stirring with adsorption contact times of 0, 5, 10, 15, 20, 30, 60, 90, 100, 120, 150, and 180 min. In the variation of concentration and temperature, concentrations of 60 mg/L, 70 mg/L, 80 mg/L, 90 mg/L, and 100 mg/L with temperature variations of 30°C, 40°C, 50°C, and 60°C were used (Zubair et al, 2022;Yuliasari et al, 2022;Liao et al, 2022). The solutions were stirred for two hours.…”
Section: Adsorption Of Color Substancesmentioning
confidence: 99%
“…Rathee et al (2019) reported that layered double hydroxide applied as an adsorbent has limitations in the regeneration process. According to Normah et al (2021) and Yuliasari et al (2022), LDH tends to have unstable adsorption effectiveness due to damage to the layer structure during the application process. To create a composite, layered double hydroxide must be changed with supporting elements made of carbon.…”
Section: Introductionmentioning
confidence: 99%